Correlation between P-glycoprotein and CD34 Expressions in Leukemic Cells from De novo Acute Myeloid Leukemia - Yulia Nadar Indrasari; Yetti Hernaningsih; Aryati Aryati; Siprianus Ugroseno Yudho Bintoro; Atika Atika; Rosline Hassan (Biomolecular and Health Science Journal)
Introduction: Acute myeloid leukemia (AML) is a clonal cancer that develops from myeloid progenitors. P-glycoprotein (Pgp) is the membrane transporter encoded by the multidrug resistance (MDR1) gene, which is responsible for the efflux of several chemotherapeutic drugs for the treatment of AML. Pgp’s physiological role in normal cells is unknown. This contrasts with the lack of clarity on Pgp’s activity as an efflux pump in neoplastic or cancer cells. The association between Pgp and CD34 expression in adult patients with de novo AML was investigated in this study. Methods: Thirty participants were enrolled between November 2022 and April 2023. Immunophenotyping, Pgp percentage, and CD34 expression examinations using bone marrow aspirate blood were performed using immunoflowcytometry. The analysis of the correlation test was performed by Spearman correlation. Results: Patients with de novo AML had a median age of 42.5 years. The bone marrow aspiration results of adult patients with AML reveal the following distribution according to the French–American–British classification: 30% of patients have AML M1, 30% have AML M2, 13.33% have AML M3, 3.33% have AML M4, 16.66% have AML M5, and 6.66% have AML M7. There was no statistical correlation between Pgp and CD34 (P = 0.063), neither Pgp and leukocyte count (P = 0.442). Conclusions: Although no correlation between Pgp with CD34 or leukocyte count, it is necessary to consider the role of other members of the ABC transporter superfamily to further examine its relationship with CD34.